A referenciação nas crônicas de Otto Lara Resende - Gonzalez, Ednel Benedita Squiapati Seragini (2009)
This research paper focuses on the reference process presented in Otto Lara Resende´s chronicles. Based on Textual Linguistics and Functionalism, we analyzed thirty-four chronicles aiming to verify the intra-discursive mechanisms of the reference process. Chronicle was defined as a discursive genre based on Bakhtin’s studies and the Otto Lara Resende’s selected chronicles, published between 1991 and 1992, were analyzed in order to verify their textual organization with the use of the reference process. According to the analysis, this research paper found out that Otto Lara Resende’s chronicles implant to the gender a literary tone exceeding the reader’s expectation due to the proper use of the reference mechanisms used by the author in the organization of his texts. In Otto Lara Resende’s works, it is possible to discover a text in which the want to say harmonizes with the way to say, really particular in the literary text. Keywords: reference, chronicle, textual linguistics, Otto Lara Resende.